The song at the end of the future: on the (mouse) people. Issue 5 (4th May 2022) - Stables, Wayne
ABSTRACT: 'The people' haunts democracy, and the sovereignty of the modern state presupposes its will: the social contract of equal and autonomous individuals. But if the power of the state derives from this spectre, the injunction to conceptualise it – or to lay it to rest – faces a double bind. On the one hand, to appeal to a unified body is to reduce difference to the order of the same, at worst yielding to a totalitarian ideal. On the other hand, to abandon the community is tantamount to an affirmation of the status quo, foreclosing the possibility of collective resistance to capitalism. In light of this predicament, this paper revisits the efforts by Jean-Luc Nancy and Maurice Blanchot, amongst others, to conceptualise the community as inoperative. What are the political implications of predicating 'the people' on alterity? Is such a turn a dereliction of the commitment to emancipatory politics or in fact a means to revitalise it? It is suggested that Franz Kafka's last story, 'Josefine, the Singer or the Mouse People [Josefine, die Sängerin oder das Volk der Mäuse]', answers compellingly to these questions.